Development Communication Innovation Patterns to Increase Community Participation in Tourism Activities in Penyengat Island - RD Rita Ritasari; Ahmad Sihabudin; Yohanes Sulistyadi; Ridzki Rinanto Sigit (International Journal of Travel, Hospitality and Events, 2024)
Purpose: This study aims to measure the level of community participation, analyze communication patterns, and formulate communication strategies and communication innovation patterns to increase community participation in tourism activities. Research methods: The level of community participation was measured by structured interviews and questionnaire instruments and analyzed using the IBM SPSS Statistics 26 with Arnstein's participation typology. Communication patterns and communication strategies to increase participation were obtained through focus group discussions (FGD) with Penyengat Island tourism stakeholders and in-depth interviews with respondents and key informants. Results and discussion: The results of this study indicate that community participation in tourism activities is found in participation in Pokdarwis activities, training and capacity building for business actors, as well as monitoring and evaluation of tourism activities. The typology of participation is in the manipulative category, with a lack of community participation in planning activities and tending to only be executors of government programs. Implication: The communication pattern applied is only limited to linear communication with no reciprocity from the communicator to the communicant, so a participatory communication strategy is needed that allows circular communication to increase community participation in tourism activities.   Keywords: Development Communication, Linear Communication, Tourism, Participation